Nostalgia as an affective complex: neuropsychological, evolutionary, personal, and social dimensions - LYTVYN, Serhiy; KROTENKO, Anastasiia; SAYENKO, Oleksandra (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. Nostalgia is explored as a complex affective phenomenon that serves functions of identity reconstruction, adaptation to loss, and the maintenance of internal stability. It is shown that nostalgia is not among the basic emotions, yet it comprises components of several primary affects. Results. The main classifications of nostalgia are analyzed (temporal, spatial, social, and individual), along with its distinction from other emotional processes. Within C. Izard’s theory, nostalgia is presented as a secondary emotion integrating sadness, joy, interest, shame, and fear. According to J. Panksepp’s model, the core systems involved are PANIC/GRIEF, CARE, SEEKING, FEAR, and PLAY. The evolutionary significance of the PANIC/GRIEF system is highlighted as a mechanism promoting social bonding. Neurophysiological and neurochemical correlates are outlined, including the involvement of the prefrontal cortex, hippocampus, amygdala, oxytocin, and endogenous opioids. The importance of bodily expression and subjective experience is examined. Cognitive aspects are described, particularly the relationship between nostalgia and autobiographical, emotional, and sensory memory. Dysfunctional forms of nostalgic experience are identified. The link between nostalgia and Big Five personality traits is considered, as well as genetic factors influencing the propensity for nostalgic experience. Particular emphasis is placed on the significance of the bodily components of nostalgic experience as markers of emotional involvement and deep self-identification. The therapeutic potential of nostalgia is revealed as an affective resource that facilitates psychological recovery, self-reflection, and reduction of emotional stress under conditions of social uncertainty. Its capacity to actualize elements of cultural memory, thereby contributing to the preservation of collective identity, is also highlighted. Cultural, religious, and political dimensions of nostalgia are also summarized. Conclusions. The conclusion emphasizes the role of nostalgia as an integrative affective mechanism that ensures continuity of experience, supports identity, and holds adaptive significance under conditions of change.